Some Problems of Thalassemia in Jakarta - Iskandar Wahidiyat; A.H. Markum; M. Abdulsalam; S. Muslichan (Paediatrica Indonesiana, 1978)
Within 10 years (1964 - 1974) two hundred and twenty one thalassemic children were observed in the Department of Child Health, Medical School, University of Indonesia in Jakarta. They consisted of 119 cases of thalassemia major, 95 thalassemia Hb E disease, 6 Hb H disease and 1 thalassemia Hb S disease. The main treatment of thalassemia major is still blood transfusion. Splenectomy was performed on 29 children with thalassemia major and 26 cases with thalassemia Hb E disease. Splenectomy performed on cases before hypersplenism appeared, showed better results then those late cases who have already symptoms of hypersplenism. Beside the medical points of view thalassemia has also many social aspects to be considered, those of the child itself, the parents and the society or community.